The effect of circulating cytokines on cardiovascular patients infected with the Coronavirus - Ruqaya Yahya Abd AL-Shaheed; Huda Jameel Baker AL-Khilkhali (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The coronavirus illness (COVID-19) is caused by serious acute respiratory disorder coronavirus 2 (SARS-CoV-2), moreover known as the COVID-19 virus. After the first-ever reports of COVID-19 in December 2019, the malady spread quickly. In January 2020, the WHO announced the outbreak a Public Health Emergency of Worldwide Concern, and by March 2020, the WHO characterized the episode as a global widespread . The current study aimed to detect the effect of SARS-CoV-2 infection in heart patients and study their immune response by detecting the levels of some cytokines, which may end in a cytokine storm and may lead to death. In this study, one hundred-eight subjects were enrolled on two comparison case-control groups, the case group included 54 patients suffering from SARS-COV2, all were selected from those who were admitted to the Intensive Care Unit (ICU), and were diagnosed by a specialist physician with severe acute respiratory syndrome due to SARS-COV2 documented by Real-Time Polymerase Chain Reaction( RT-PCR ) besides other clinical and laboratory criteria in Marjan Medical City in Babylon province, AL-Amal Hospital for Communicable Diseases and AL-Hakeem Hospital, Najaf/Iraq , for a period from March 2022 to October 2022 to evaluate the role of some selected serological among patients with SARA-COV2 . The control group in this study included 54 subjects, divided into three groups (Apparent Healthy, patients suffered from SARS-COV2, patients suffered from CVD). Blood samples were examined through immunological methods, and an enzyme-linked immunosorbent assay (ELISA) was adopted for the detection of the concentration of TNF-α, IL6, IL-10,1L-12 and CCL2 .The immunological evaluation to clarify the theory of cytokines storm carried in the present study revealed that (TNF-α, IL6, IL-10,1L-12, and CCL2) for patients with COVID-19 and CVD was significantly higher than all the comparison group . The study reported that interleukin (6, 10, 12) and TNF-a are significantly increased in patients with covid19, CVD, and COVID-19 patients only, compared to healthy people. furthermore, IL-6 and IL-12 levels increased in patients with CVD only when compared to healthy people. There is a significant increase in CCL2 in all study groups compared to healthy people who have lower levels and this study indicated that the infection with Covid disease was severe and critical in most patients with CVD. This increased the number of deaths among them.